DESAIN DAN PENERAPAN APLIKASI LAPORAN PERSEDIAAN BARANG MASUK DAN KELUAR DI APOTEK PBSA BABAT TOMAN - Dian, Dian Ofasari; Meilansari, Selvita; Oktarida, Anggeraini (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2025)
Information technology can be used optimally to build a reliable accounting system, especially for trading companies with high sales volumes. A computerized stock control system is very beneficial in managing recurring sales transactions. In addition, this system simplifies the generation of accurate stock level reports, which are very important for monitoring inventory balances over a certain period. This research aims to assist PBSA Pharmacy in providing relevant stock information that is effective and efficient in terms of time and effort. Primary and secondary data were collected through documentation and interviews and analyzed descriptively qualitatively. Based on interviews, PBSA pharmacies still face difficulties in obtaining accurate and efficient stock information. However, with the implementation of the designed accounting information system, PBSA pharmacy has faster and more accurate access to the information needed, switching from manual recording to a computer-based system.